Cart Related Trauma in Paediatrics: Revision of 54 Injured Child in Central, Sudan - Tewfiq, Suha; Nugud, Faisal; Mohammed, Omer A.; Taha, Osman (Gezira Journal of Health Sciences, 2016)
Abstract: Background : Many children are admitted to the National Centre of Paediatric Surgery (NCPS), Gezira State- Sudan because of Cart-related trauma(CRT), those children reside in informal settlements, where there is lack of water supply, so they use a donkey- drawn water cart .Worldwide 78% of lethally injured children die before hospital arrival , demonstrating the need for effective injury prevention. > Objectives : To describe the mechanism of injury, demonstrate the epidemiological parameters of injury and to suggest preventive measures. Design: hospital –based descriptive cross sectional prospective study involved all children admitted to the NCPS because of CRT Between June 2011 and June 2013. Results : Between (June 2011 - June 2013), 54 paediatric patients admitted to the NCPS with CRT, the median age was 9.6 yrs, 92% were males, 97% from rural areas and 3% from suburbs , the most frequent injury diagnosed was Abdominal injuries in 44 patients (81.4%), followed by chest injury( n=6) 11.1%, extremities injury n=3 (5.5%) and the least was head injury 1 patient (1.85%) and the overall mortality was 1.8%(n= 1) died on arrival to hospital because of severe head injury. The mechanism of trauma was demonstrated, the cart of class- I leaver system and the force causing the injury was calculated. Conclusion: The study highlights the morbidity and mortality of Cart-related trauma in central Sudan, it also documents the usefulness of institutional trauma data base in identifying common traumatic injuries in paediatric, which is required for identifying appropriate public health measures and directing resources towards the prevention and management of trauma.